Study of Two-layer System TiN / Ni 0.905 W 0.095 Adoptable for Creating Paramagnetic Substrates with Cubic Texture for 2G HTS Superconductors (Global Journal of Science Frontier Research, 2021)
The influence of deposition conditions on the morphology and structure of the two-layer system TiN / Ni 0.905 W 0.095 were studied. The effect of concurrent formation of cube texture both in substrate based on paramagnetic alloy Ni 0.905 W 0.095 and TiN coating was detected by means of xray diffraction analysis. Composition TiN / Ni 0.905 W 0.095 may be used as a substrate in the conductive architecture of 2G HTS to improve its critical current density.
Keywords: 2G HTS; superconductivity; cubic texture; TiN; Ni-W; buffer layer; paramagnetic substrate